SYSTEMATIC LITERATURE REVIEW: MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Fizadella, Revita Amanda (UNIVERSITAS TANJUNGPURA, 2024)
The contradictory between the urgency of mathematical reasoning ability and the facts in the field resulted in the need for the application of the Discovery Learning model in learning. This study uses the Systematic Literature Review method which aims to see the development of various studies on the Discovery Learning model on mathematical reasoning skills. This study analyzed 20 articles in the range of 2018-2024 where it was found that the research trend was in 2018, with research subjects at the junior high school, on the material of building space, and research trends using quantitative methods. In general, the results show that the Discovery Learning model has a positive impact on students' mathematical reasoning skills